2012
DOI: 10.1371/journal.pone.0047490
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus-Specific miRNAs and Argonaute2 Play a Role in the Viral Life Cycle

Abstract: Disease-specific serum miRNA profiles may serve as biomarkers and might reveal potential new avenues for therapy. An HBV-specific serum miRNA profile associated with HBV surface antigen (HBsAg) particles has recently been reported, and AGO2 and miRNAs have been shown to be stably associated with HBsAg in serum. We identified HBV-associated serum miRNAs using the Toray 3D array system in 10 healthy controls and 10 patients with chronic hepatitis B virus (HBV) infection. 19 selected miRNAs were then measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 49 publications
2
53
3
Order By: Relevance
“…Our data suggest a net negative impact of the microRNA machinery on HBV replication, which is contradictory to a recent report indicating a positive role of Ago2 in HBV replication (23). To address this discrepancy, we further tested knocking down the essential component of the microprocessor DGCR8 and the microRNA maturation factor Dicer, both of which were efficiently down-regulated in siRNA-treated cells (data not shown).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data suggest a net negative impact of the microRNA machinery on HBV replication, which is contradictory to a recent report indicating a positive role of Ago2 in HBV replication (23). To address this discrepancy, we further tested knocking down the essential component of the microprocessor DGCR8 and the microRNA maturation factor Dicer, both of which were efficiently down-regulated in siRNA-treated cells (data not shown).…”
Section: Resultscontrasting
confidence: 99%
“…by knocking down Ago2), we demonstrated that inactivation of the microRNA machinery benefits HBV replication in HepG2 cells. Our results disagree with a recent report indicating that a siRNA against Ago2 impaired HBV replication in T23 cells (23). Although the source for this discrepancy remains unclear, we note that T23 cells carry an integrated HBV genome whereas our experiments were performed on freshly transfected HepG2 cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Analysis of differential microRNA expression in liver tissues has revealed HCV-and HBV-specific microRNAs as well as microRNAs associated with the stage of liver disease. 5e9 MicroRNA levels in the liver have been found to be correlated with serum levels for a number of microRNAs, 10,11 suggesting that serum microRNAs might act as a surrogate measure of microRNA activity in the liver. While RNA typically has a short-half life and is quickly degraded by RNases, microRNAs tend to exist stably in serum when bound to argonaute proteins such as AGO2 as part of the RNA-induced silencing complex, the molecular scaffold that facilitates interaction of a microRNA with its target sequence.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction is presumed to be important for the intracellular movement of viral components. Hepatitis B virus (HBV), core (HBc), and surface (HBs) proteins but not HBx protein interact and colocalize with Ago2 in the ER and other subcellular compartments, while Ago2 appears to play a role in HBV life cycle (Hayes et al, 2012). The Kaposi's sarcoma-associated herpesvirus SOX protein induces internal cleavage of host mRNA, which are then degraded by the 5¢-3¢ cellular exonuclease Xrn1 (Covarrubias et al, 2011).…”
Section: Pb Constituents That Support Virus Replicationmentioning
confidence: 99%